2018
DOI: 10.1155/2018/5125103
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Ubiquitination Sites Using UbiNets

Abstract: Ubiquitination controls the activity of various proteins and belongs to posttranslational modification. Various machine learning techniques are taken for prediction of ubiquitination sites in protein sequences. The paper proposes a new MLP architecture, named UbiNets, which is based on Densely Connected Convolutional Neural Networks (DenseNet). Computational machine learning techniques, such as Random Forest Classifier, Gradient Boosting Machines, and Multilayer Perceptrons (MLP), are taken for analysis. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…Our results demonstrated that DL approaches outperformed traditional ML techniques across various evaluation metrics, specifically achieving a macro-F1 score of 0.574 compared to 0.537. Specifically, in contrast to many customized-designed DL network architectures [ 71 ], we found that the LSTM architecture achieved the highest macro-F1 score using only raw amino acid sequences as input. This finding is consistent with previous research [ 14 , 28 ] and shows the capability of DNN architectures to automatically learn meaningful features from protein sequences for ubiquitination site prediction.…”
Section: Discussioncontrasting
confidence: 68%
“…Our results demonstrated that DL approaches outperformed traditional ML techniques across various evaluation metrics, specifically achieving a macro-F1 score of 0.574 compared to 0.537. Specifically, in contrast to many customized-designed DL network architectures [ 71 ], we found that the LSTM architecture achieved the highest macro-F1 score using only raw amino acid sequences as input. This finding is consistent with previous research [ 14 , 28 ] and shows the capability of DNN architectures to automatically learn meaningful features from protein sequences for ubiquitination site prediction.…”
Section: Discussioncontrasting
confidence: 68%
“…Another predictor, ESA-UbiSite, which is based on an evolutionary screening algorithm (ESA), uses a set of well-selected physicochemical properties together with an SVM for accurate prediction. In the literature, deep learning models that include UbiNets use densely connected neural networks [ 55 ]. DeepUbi uses a convolutional neural network (CNN) [ 56 ] and Caps-Ubi uses a capsule network [ 57 ].…”
Section: Introductionmentioning
confidence: 99%